2012
DOI: 10.1021/mp300334r
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein, Breast Cancer Resistance Protein, Organic Anion Transporter 3, and Transporting Peptide 1a4 during Blood–Brain Barrier Maturation: Involvement of Wnt/β-Catenin and Endothelin-1 Signaling

Abstract: Our current knowledge about drug transporters in the maturational brain is very limited. In this study, we provide a comprehensive overview of the expression and activity profile of P-glycoprotein (P-gp), Breast Cancer Resistance Protein (bcrp), Organic Anion Transporter 3 (oat3), and Transporting Peptide 1a4 (oatp1a4) transporters during blood-brain barrier (BBB) maturation. Gene and protein expressions of the analyzed transporters increase as the brain matures, with no variation in their activity for P-gp an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…Little information has been published concerning the ontogeny of Mrps and Bcrp genes in the BBB. Bcrp expression in rat brain microvessels was shown to increase after P2 . The presented BCRP efflux activity results did not show maturation in BCRP activity at the BBB level, although Abcg2 gene expression significantly increased between P14 and P56.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Little information has been published concerning the ontogeny of Mrps and Bcrp genes in the BBB. Bcrp expression in rat brain microvessels was shown to increase after P2 . The presented BCRP efflux activity results did not show maturation in BCRP activity at the BBB level, although Abcg2 gene expression significantly increased between P14 and P56.…”
Section: Discussionmentioning
confidence: 63%
“…Our results show, therefore, a maturational increase in BBB P-gP activity during brain development. Previous studies had reported no difference in P-gP efflux activity between immature and adult rats [9]. Nonetheless, in mice embryos, rhodamine-123 efflux coincides with the increased Figure 2 Expression levels Ontogeny of selected SLC transporters in isolated rat brain microvessels at post-natal days 14, 21, and 56 (P14, P21, and P56, respectively).…”
Section: Discussionmentioning
confidence: 87%
“…Bumetanide is a reported substrate of oat3, which is present at the BBB. [27,28] Even though probenecid can inhibit other oat transporters, oat3 is the only member of the family of transporters that has been detected in rat BCEC. [29,30,54] Thus, any increase in brain bumetanide that was independent of changes in plasma bumetanide could be attributed to the inhibition of efflux by oat3 at the rat BBB.…”
Section: Discussionmentioning
confidence: 99%
“…[10,22,23] In addition, bumetanide has been reported to be a substrate of organic anion transporter 3, both human (OAT3) and rodent (oat3). [24][25][26][27][28] OAT3/oat3 is predominantly expressed in two sites within the body, the basolateral membrane of proximal renal tubule cells, and the basolateral side of the BBB. [29,30] OAT3 is an efflux transporter involved in effluxing anions, such as bumetanide, from the blood into renal tubule cells, and from the brain via the BBB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation